2020
DOI: 10.1371/journal.pone.0228357
|View full text |Cite
|
Sign up to set email alerts
|

Paternal exposure to a common herbicide alters the behavior and serotonergic system of zebrafish offspring

Abstract: Increasingly, studies are revealing that endocrine disrupting chemicals (EDCs) can alter animal behavior. Early life exposure to EDCs may permanently alter phenotypes through to adulthood. In addition, the effects of EDCs may not be isolated to a single generation − offspring may indirectly be impacted, via non-genetic processes. Here, we analyzed the effects of paternal atrazine exposure on behavioral traits (distance moved, exploration, bottomdwelling time, latency to enter the top zone, and interaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 136 publications
(155 reference statements)
4
16
0
Order By: Relevance
“…This conclusion was confirmed in the novel object recognition test [ 97 ]. In zebrafish, it was also observed that paternal atrazine exposure at 0.3, 3, or 30 ppb had intergenerational dysfunction of the serotonergic system in the offspring [ 98 ]. Although only a few limited studies have been completed, each gives support that atrazine may interfere with the serotonergic system with potential for sex-specific responses at doses near or below the current chronic dietary NOAEL at 1.8 mg/kg/day.…”
Section: Effects Of Atrazine On Major Neurotransmittersmentioning
confidence: 99%
“…This conclusion was confirmed in the novel object recognition test [ 97 ]. In zebrafish, it was also observed that paternal atrazine exposure at 0.3, 3, or 30 ppb had intergenerational dysfunction of the serotonergic system in the offspring [ 98 ]. Although only a few limited studies have been completed, each gives support that atrazine may interfere with the serotonergic system with potential for sex-specific responses at doses near or below the current chronic dietary NOAEL at 1.8 mg/kg/day.…”
Section: Effects Of Atrazine On Major Neurotransmittersmentioning
confidence: 99%
“…Knowing the negative infl uence of atrazine on the reproductive system, this agent was included in the list of endocrine disrupting chemicals by some organizations and countries, such as the European Community, Japan, and the United States, as it has environmental estrogenic activity with carcinogenic potential and that it can persist in the environment for long periods [16]. The mechanism underlying neuroendocrine interference caused by atrazine remains to be elucidated, but it is known to be involved in the disruption of many pathways, including the Hypothalamic-Pituitary-Gonadal (HHG) axis, monoaminergic systems in the central nervous system, changes in cyclic Adenosine Monophosphate (cAMP)-dependent signaling pathway, as well as in epigenetic mechanisms, including microRNAs and expression of DNA methyltransferases [26]. Results of a systematic literature review conducted by Wirbisky and a study was demonstrated that atrazine aff ects the HHG axis, with eff ects on the reproductive and endocrine systems in rats and with diff erences depending on the stage of life, dose, duration of exposure and strain of rats used.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, a study by Lamb evaluated the eff ects on male off spring of zebrafi sh exposed to doses of 0.3, 3 or 3 Parts Per Billion (ppb) of atrazine; their fi ndings showed that endocrine and neuroendocrine disrupting chemicals can alter or interrupt some animal behaviors, especially typical reproductive behaviors, but can also lead to anxiety, aggression, and risky behavior, especially when exposure to these agents occurs early in life [26]. Thus, the scientifi c literature shows that early exposure to endocrine disruptors can permanently modify phenotypes behavior of the animal until adulthood, interfering with molecular mechanisms such as gene expression, hormone levels and neurotransmitter levels.…”
Section: Figurementioning
confidence: 99%
“…Progeny from five families per treatment (n=5 hypoxia, n=5 control) were generated by in vitro fertilisation (IVF) (Johnson Sheri L. et al, 2018;Lamb et al, 2020) seven days after parental exposure finished. Briefly, eggs and sperm were collected using abdominal massage -half the sperm was used for IVF and the other half was stored for subsequent DNA extraction.…”
Section: Hypoxia Tolerance Assays and Analysismentioning
confidence: 99%
“…Here we use zebrafish to further explore the phenomenon of transgenerational acclimation of hypoxia in fishes. We focus on paternal exposure as we predict that environmental specific information can be transferred via sperm, as observed in other studies (Dias and Ressler, 2013;Lamb et al, 2020;Wang et al, 2016). We test whether paternal exposure to hypoxia stimulates phenotypic responses in offspring, using behavioural phenotyping to identify resistance to acute hypoxia (time to loss of equilibrium).…”
Section: Introductionmentioning
confidence: 99%